Hotel Ponce de Leon : the rise, fall, and rebirth of Flagler's gilded age palace - Keys, Leslee F. (University Press of Florida, 2015)
Keys details the famous Hotel Ponce de Leon building (currently Flagler College) and preservation efforts to reclaim the former hotel to its gilded age glory.